PENDEKATAN PENDIDIKAN ISLAM DALAM KAJIAN STUDI ISLAM - Mahariah Mahariah; Muhammad Shaleh Assingkily (Tazkiya: Jurnal Pendidikan Islam, 2021)
This article aims to analyze the approach to Islamic education in the study of Islamic studies. This research uses a qualitative approach with a literature study method. Research analysis is carried out using literature or scientific reference materials. Through this research, it was found that by developing approaches in Islamic education so as to broaden understanding and encourage people to practice them and at the same time shape their character and personality. The relationship between man and God is a basic requirement for success in the relationship between man and his environment. If the relationship between God and humans is more structured, more assertive and runs according to the criteria set by Allah, the relationship between humans and the environment will be more successful, as well as in Islamic education.Keywords: Approach, Islamic Education, Islamic Studies